Tourism and economic growth: The role of globalization - Hidayati, Firda (FIA UB, 2017)
Tourism is believed to bring significant impact on economic growth in both developed and developing countries.. However, many still question the role of globalization to foster tourism impact on economic growth. This research amied to review current journals on tourism to examine possible impacts of globalization on tourism and economic growth. This study is aimed to review articles from 2007 to 2017 (10 years)Â to map the correlation between those three aspects. The finding supports the notion on the positive impact of globalization to tourism contribution to economic growth. Â The developing and third world countries need to manage globalization, in term of export, Foreign Direct Investment (FDI) and foreign tourist spending to increase tourism developement and economic growth. Proper tourism expansion policy should not only focus on physical insrastructure such as hotels, roads, and restourants, but also no-physical infrastructucture such as innovation and coordination to enhance benefits gained from globalization. The key to increase tourism effectiveness is innovation, therefore, tourism policy should be equipped with education system that allows local officers and society to adapt with constant change and multiple stakeholders form different nationalities, cultures and education background.